1999
DOI: 10.1073/pnas.96.4.1291
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of type M 2 pyruvate kinase activity by the human papillomavirus type 16 E7 oncoprotein

Abstract: We report here that the E7 oncoprotein encoded by the oncogenic human papillomavirus (HPV) type 16 binds to the glycolytic enzyme type M 2 pyruvate kinase (M2-PK). M2-PK occurs in a tetrameric form with a high affinity to its substrate phosphoenolpyruvate and a dimeric form with a low affinity to phosphoenolpyruvate, and the transition between both conformations regulates the glycolytic f lux in tumor cells. The glycolytic intermediate fructose 1,6-bisphosphate induces the reassociation of the dimeric to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
212
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(224 citation statements)
references
References 37 publications
(42 reference statements)
10
212
0
2
Order By: Relevance
“…So, inhibition of expression of PKM2 may also affect the proliferation of other cells. The superiority of PKM2 compared with PKM1 might be that it can balance energy supply and glycolytic phospho-metabolite pools by switching between two quaternary conformations (12)(13)(14)(15)(16)(17)(18). As is mentioned above, PKM2 can exist as an active tetrameric and an inactive dimeric form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, inhibition of expression of PKM2 may also affect the proliferation of other cells. The superiority of PKM2 compared with PKM1 might be that it can balance energy supply and glycolytic phospho-metabolite pools by switching between two quaternary conformations (12)(13)(14)(15)(16)(17)(18). As is mentioned above, PKM2 can exist as an active tetrameric and an inactive dimeric form.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that most PKM2 exists mainly as a dimeric form in tumor cells. Some viral oncoproteins like HPV-16E7 and pp60v-Src kinase (12,13) as well as cellular phosphotyrosine signaling (14,15) can induce the dimerization of PKM2, but the Ras oncogene induces the tetramerization of PKM2 (16,17). Recently, Kosugi et al (18) found that PKM2 activity is also regulated by direct binding of oncoprotein MUC1-C. Another important metabolic regulator of PKM2 is fructose 1,6-bisphosphate.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol gradient fractionation studies indicated that PML-2KA inhibited the activity of the tetrameric form, but not the dimeric form of PKM2. HPV E7 has been previously reported to directly bind to PKM2, and to shift its tetramer-dimer equilibrium towards the dimeric state (Zwerschke et al 1999). The tetramer : dimer ratio of PKM2 is also regulated by ATP, FBP and serine (Eigenbrodt et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…1981;Eigenbrodt et al 1992;Boros et al 1997Boros et al , 2000Zwerschke et al 1999;Cascante et al 2000;Mazurek et al 2001). To address whether cPML affects the tetramer : dimer ratio of PKM2, cell lysates were prepared from control and PML-2KA-expressing MCF-7 cells and subjected to glycerolgradient centrifugation.…”
Section: Modulation Of Tetramer Pkm2 Activity By Pml-2kamentioning
confidence: 99%
“…The upregulation of the M2-PK protein is under the control of HIF-1 and ras, which are both consistently altered in gastrointestinal tumours (Kress et al, 1998;Mazurek et al, 2001;Nishikawa et al, 2002;Mazurek and Eigenbrodt, 2003). The tetramer : dimer ratio of M2-PK is under the control of several oncoproteins, such as pp60 vÀsrc kinase, HPV-16 E7 and A-Raf ( Figure 1B) (Eigenbrodt et al, 1998b;Zwerschke et al, 1999;Le Mellay et al, 2002). Interestingly, pp60 cÀsrc kinase and A-Raf are consistently altered in gastrointestinal tumours (Bolen et al, 1987;Iravani et al, 1998;Irby et al, 1999;Luckett et al, 2000;Dehm et al, 2001;Dhillon et al, 2003).…”
mentioning
confidence: 97%